2019
DOI: 10.3389/fimmu.2019.01168
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Migration of Immune Cells

Abstract: Lymphatic vessels collect interstitial fluid that has extravasated from blood vessels and return it to the circulatory system. Another important function of the lymphatic network is to facilitate immune cell migration and antigen transport from the periphery to draining lymph nodes. This migration plays a crucial role in immune surveillance, initiation of immune responses and tolerance. Here we discuss the significance and mechanisms of lymphatic migration of innate and adaptive immune cells in homeostasis, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
126
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(126 citation statements)
references
References 134 publications
0
126
0
Order By: Relevance
“…Adaptive immune responses rely on a rapid, spatiotemporally concerted migration of BMDCs to the lymph nodes or to the site of inflammation [14]. Although many parts of these process are well understood, little is known about the detailed molecular mechanisms underlying the actual migration and passage through complex tissue settings and highly confined spaces.…”
Section: Resultsmentioning
confidence: 99%
“…Adaptive immune responses rely on a rapid, spatiotemporally concerted migration of BMDCs to the lymph nodes or to the site of inflammation [14]. Although many parts of these process are well understood, little is known about the detailed molecular mechanisms underlying the actual migration and passage through complex tissue settings and highly confined spaces.…”
Section: Resultsmentioning
confidence: 99%
“…Memory T cells also enter initial lymphatics [25]. Tissue-resident memory cells lack CCR7, but migrating memory T cells express CCR7 and have the capacity to enter initial LVs, following the CCL21 gradient guidance [32]. T cell entry into afferent lymphatics is regulated by the bioactive lipid sphingosine-1-phosphate (S1P), which activates specific S1P receptors on the surface of T lymphocytes to direct migration [33].…”
Section: Lvs Serve As a Bridge Between Innate And Adaptive Immunitymentioning
confidence: 99%
“…In our study, we showed that the PDT protocol was associated with a larger upregulation of CCR7 than that induced by LPS (however, this is known as a potent inducer of the migratory capacity of DC [31]). The high surface expression of CCR7 is associated with a high migratory responsiveness to the lymphatic-produced chemokines CCL19 and CCL21 [32][33][34]. Remarkably, we could document the increased motility of DCs in the minutes following i.p.…”
Section: Discussionmentioning
confidence: 54%